Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan di PT. Melali MICE Bali - I Putu Gede Satria Wiraharja (Journal of Hospitality Accommodation Management (JHAM), 2022)
This study aims to analyze the influence of work motivation on employee performance in PT. Melali MICE Bali, using Herzberg's 2 factor theory to analyze work motivation and 5 indicators to measure the performance proposed by Stephen P. Robbins. The technique to determine the sample by using nonprobability sampling technique that makes the entire population into a sample that is 19 respondents who are employees of PT. Melali MICE Bali data taken through questionnaire, validity test, reliability, normality, multicolinearity, heteroskedasity, multiple linear regression, multiple correlation, t-test, and f-test with the help of SPSS program version 23. Then obtained data showing the test device Used valid and reliabel with normal distribution, and result of analysis showing existence of influence of strong and significant relation between work motivation to employee performance equal to 97,7% which is the magnitude of the contribution of the influence of the x variable to the y variable. The findings of this study are expected to be able to be developed by the next researcher by adding new variables.